2020
DOI: 10.1021/acs.jmedchem.9b01563
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Activity against Multidrug-Resistant Bacteria through Coapplication of an Analogue of Tachyplesin I and an Inhibitor of the QseC/B Signaling Pathway

Abstract: Tachyplesin I (TPI) is a cationic β-hairpin antimicrobial peptide with broad-spectrum, potent antimicrobial activity. In this study, the all D-amino acid analogue of TPI (TPAD) was synthesized, and its structure and activity were determined. TPAD has comparable antibacterial activity to TPI on 14 bacterial strains, including four drug-resistant bacteria. Importantly, TPAD has significantly improved stability against enzymatic degradation and decreased hemolytic activity compared to TPI, indicating that it has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Tachyplesin I (TPI, 60 ) is a 14-amino acid β-hairpin anti-microbial peptide with two disulfide bonds originally isolated from the hepatocytes of Tachypleus tridentatus [ 70 ]. Replacement of all L-amino acids with D-amino acids in TPI generated TPAD ( 61 ) which retained the anti-microbial activity (MIC values about 8 μg/mL against P. aeruginosa ) and showed improved enzymatic stability as well as decreased hemolytic activity [ 71 ]. Mechanism study revealed that the activation of the quorum sensing E. coli regulators B and C (QseC/B) two-component system induced the bacterial resistance to peptide 61 , while the combination of 61 with QseC/B inhibitor obviously increased the bactericidal effect against several multidrug-resistant bacteria.…”
Section: Emerging Mnps As Promising Antibiotics For Inhibiting ...mentioning
confidence: 99%
“…Tachyplesin I (TPI, 60 ) is a 14-amino acid β-hairpin anti-microbial peptide with two disulfide bonds originally isolated from the hepatocytes of Tachypleus tridentatus [ 70 ]. Replacement of all L-amino acids with D-amino acids in TPI generated TPAD ( 61 ) which retained the anti-microbial activity (MIC values about 8 μg/mL against P. aeruginosa ) and showed improved enzymatic stability as well as decreased hemolytic activity [ 71 ]. Mechanism study revealed that the activation of the quorum sensing E. coli regulators B and C (QseC/B) two-component system induced the bacterial resistance to peptide 61 , while the combination of 61 with QseC/B inhibitor obviously increased the bactericidal effect against several multidrug-resistant bacteria.…”
Section: Emerging Mnps As Promising Antibiotics For Inhibiting ...mentioning
confidence: 99%
“…Tachyplesin I, from the hemocytes of the horseshoe crab Tachypleus tridentatus , [ 139 ] has broad antimicrobial activity against Gram‐positive and Gram‐negative bacteria, [ 140,142,157–159 ] as well as anti‐fungal, [ 140 ] anti‐viral [ 160 ] and anti‐cancer activity. [ 142,161 ] Despite its antimicrobial activity, the toxicity of tachyplesin I toward mammalian cells limits its clinical application.…”
Section: Antimicrobial Cpps To Target Drug‐resistant Bacteria Inside ...mentioning
confidence: 99%
“…Wang et al. synthesized all D‐amino acid‐modified Tachyplesin‐1 which exhibits decreased hemolytic activity and enhanced stability compared to the unmodified Tachyplesin‐1 . Moreover, the D‐amino acid‐modified Tachyplesin‐1 showed comparable antibacterial activity including drug‐resistant bacteria.…”
Section: β‐Hairpin Antimicrobial Peptidesmentioning
confidence: 99%